The use of Pillcam Colon in assessing mucosal inflammation in ulcerative colitis: a multicenter study - Sung, J.; Ho, K. Y.; Chiu, H. M.; Ching, J.; Travis, S.; Peled, R. (Endoscopy, 2012)
Background and study aim: Treatment of ulcerative colitis should be tailored to the severity of colonic inflammation, which in the past has been gauged mainly by clinical features and biochemical parameters. Recently, mucosal healing has been proposed as a standard to guide therapy. The aim of this multicenter study was to test whether mucosal appearance, as reported by colon capsule endoscopy (CCE), can be used to differentiate active from inactive ulcerative colitis. Patients and methods: Adult patients from Hong Kong, Singapore, and Taiwan who were suspected or known to have ulcerative colitis were included in this prospective study. CCE and conventional optical colonoscopy were offered to these patients on the same day after receiving standard bowel preparation. The primary endpoint was the accuracy of CCE in assessing colonic inflammation (defined as the presence of ulcers, erythema, erosions, edema, exudates in mucosa), using optical colonoscopy as the gold standard. Results: At total of 100 patients (42 females; median age 50 years; range 22 – 68 years) were enrolled. Four cases were excluded from the analysis due to technical failure or slow transit of the capsule. In nine patients, the capsule was not excreted within 8.5 hours and required retrieval during colonoscopy. The sensitivity of CCE to detect active colonic inflammation was 89 % (95 % confidence interval [CI] 80 – 95) and specificity was 75 % (95 %CI 51 – 90). The positive and negative predictive values of CCE for colonic inflammation were 93 % (95 %CI 84 – 97) and 65 % (95 %CI 43 – 83), respectively. No serious adverse event related to the CCE procedure or preparation was reported. Conclusion: CCE is a safe procedure to monitor mucosal healing in ulcerative colitis. However, at this stage, CCE cannot be recommended to replace conventional colonoscopy in the management of this condition.